The role of eco-innovation in market shaping strategies - Kazemian, Seyedehpegah (My University, 2024)
Eco-innovation and market shaping phenomena both are new fragmented concepts, and more research is needed on these two topics to identify the key factors and drivers of them. Therefore, the aim of this research is to study and present how the existing literature has examined different elements of eco-innovation and market shaping, to develop a framework for connecting these two topics. To achieve this purpose of the study, the author has conducted qualitative research by reviewing literatures through Web of Science (WoS) and Google Scholars. Several criteria were assessed as inclusion and exclusion steps to exclude the irrelevant studies. The data were analysed utilizing content analysis. The analysed articles revealed that eco-innovation has an impact on market shaping strategies inside firms and provided insights into the eco-innovation multi-levels drivers that positively affect the adaption of market shaping strategies. Thus, according to the final study framework, macro-level drivers of eco-innovation including governmental regulations and policy instruments, meso-level eco-innovation drivers including market demands, financing availability and pressure groups, and micro-level eco-innovation drivers including firm’s characteristics, business strategy, and technological competences can foster the adaption and employment of market shaping strategies. Therefore, understanding the drivers of eco-innovation in different levels and implementing eco-innovation in organizations’ strategies can help to shape and move the markets towards sustainability. This study offers valuable insights both in theory and practice for researchers and managers in organizations. Theoretically, the research examines the relationship between eco-innovation and market shaping strategies and practically, it provides valuable recommendations for business managers and give them insights into moving towards sustainable markets.
Keywords: eco-innovation, market shaping